PROYEK BUKU ANTOLOGI PUISI DAPAT MENINGKATKAN KEMAMPUAN MENULIS PUISI SISWA - Marisa Monika (Jurnal Pendidikan Dasar, 2020)
Based on the field observation, the students’ poem writing skill was very low. One of the problems was uninteresting model of learning implementation by the teacher. Based on the study, project based learning model could create very interesting learning environment, collaborative, and give a chance to students to explore their writing skill and create a product from their though and creativity. In this study, the implementation of project based learning model can stimulate students to write down the idea in literature work. Poem anthology book which was distributed become an ISBN book is a product from the implementation of project based learning. This book is compilations of students’ poem that is consist of various themes that were taken from students’ life experiences. So, we can conclude that this book can improve elementary students’ poem writing skill.